2019
DOI: 10.1002/pmh.1446
|View full text |Cite
|
Sign up to set email alerts
|

Lack of meaning, purpose and direction in life in personality disorder: A comparative quantitative approach using Livesley's General Assessment of Personality Disorder

Abstract: Meaning in life is a motivational force and an existential theme for many people. The concept of meaning comprises purpose, comprehension and mattering. According to the Section III model of personality disorder (DSM‐5), lack of meaning, purpose and direction in life is part of personality dysfunction. The present study aimed to determine the association between personality disorder (PD), personality dysfunction and ‘lack of meaning, purpose and direction’ as a distinct facet of personality dysfunction, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Similarly, individuals with histories of early childhood adversity, particularly histories of emotional and physical abuse, score lower than controls (Hill et al, 2018). And, as mentioned above, patients with a mixed group of personality disorders (diagnosed with Structured Clinical Interview for DSM-IV Personality Disorders—primarily avoidant, borderline, and not-otherwise specified, with or without concurrent depression) score lower on purpose in life measures than psychiatric patients without personality disorders and much lower than normal controls (Steen et al, 2019). Furthermore, among patients with borderline personality disorders, purpose in life ratings are inversely related to the severity of borderline personality disorder symptoms (Marco et al, 2017a).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, individuals with histories of early childhood adversity, particularly histories of emotional and physical abuse, score lower than controls (Hill et al, 2018). And, as mentioned above, patients with a mixed group of personality disorders (diagnosed with Structured Clinical Interview for DSM-IV Personality Disorders—primarily avoidant, borderline, and not-otherwise specified, with or without concurrent depression) score lower on purpose in life measures than psychiatric patients without personality disorders and much lower than normal controls (Steen et al, 2019). Furthermore, among patients with borderline personality disorders, purpose in life ratings are inversely related to the severity of borderline personality disorder symptoms (Marco et al, 2017a).…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, patients with eating disorders reported lower purpose of life than controls, and those with lower scores showed greater psychopathology including suicidal ideation (Marco et al, 2017b). Finally, patients with a variety of personality disorders also report lower purpose in life ratings than controls (Steen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is suggested that these factors were primarily related to the person, and that "personal" factors may be driven by underlying difficulties. For example, low confidence, hopelessness, levels of distress, perfectionism, and rumination (e.g., [51][52][53][54][55], may all be elements of anxiety and/or depression. Academic/clinical and youth advisors agreed that goals may become clearer over time, particularly for young people experiencing depression and purposeless, and through collaboration, goals could be formulated.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, some clinicians may avoid addressing existential and transcendent issues related to suffering, perceiving discussions about “meaning,” “purpose,” and death-related apprehensions as too “spiritual” or “philosophical” for psychiatric concern. Nevertheless, themes concerning meaning, personal dignity, and personal values pervade psychiatric complaints and problems (Marco et al, 2020; Gross et al, 2019; Steen et al, 2019). Because the absence of a sense of meaning and purpose has clearly been associated with unhealthy behaviors, poor clinical outcomes, and reduced quality of life (Gross et al, 2019; Kim et al, 2014; Steen et al, 2019), these issues are consequential to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, themes concerning meaning, personal dignity, and personal values pervade psychiatric complaints and problems (Marco et al, 2020; Gross et al, 2019; Steen et al, 2019). Because the absence of a sense of meaning and purpose has clearly been associated with unhealthy behaviors, poor clinical outcomes, and reduced quality of life (Gross et al, 2019; Kim et al, 2014; Steen et al, 2019), these issues are consequential to clinical practice. Psychotherapeutic interventions based on Yalom's (1980) existential psychotherapy and Frankl's (2005) logotherapy have illuminated and inspired generations of clinicians.…”
Section: Discussionmentioning
confidence: 99%